Majapahit Housing Roof: Analysis of Terracotta Miniature Houses - Esa P.B.G.G. Patridina; Agus Trilaksana; Gusti Ngurah Ary Kesuma Puja (Tarikhuna: Journal of History and History Education, 2024)
This research reveals the socioeconomic conditions of Majapahit society through the roofing materials of houses in the Majapahit Kingdom. The primary data consists of stroke patterns on the roof of miniature terracotta artifacts. The shape of the strokes applied to the roof suggests the type of roofing material. This research employs mixed methods. Quantitative method was used for clustering, while qualitative method was used to analyse each material individually. Production theory guided the data analysis to determine the economic level described through materials, considering factors such as: (1) overall material quality, (2) raw materials availability and accessibility and (3) production process complexity. Clustering analysis results of 183 miniature house terracotta artifacts revealed five types of strokes: (1) asymmetric strokes, likely depicting palm fibre material (Ijuk), (2) flat vertical strokes, suggesting wood plank material, (3) cylindrical vertical strokes, indicating bamboo material, (4) square sheets representing shingle or tile material, and (5) unidentified strokes. Unidentified strokes (≤18%) are representing unique artistic expressions or the absence of strokes, showcasing the creativity of terracotta craftsmen. The observed roofing materials provide insights about three economic levels within Majapahit society. Palm fibre and bamboo roofs likely indicate the lower-middle-class dwellings, plank and wood roofs suggest lower or upper-middle-class status and finally (3) shingle and tile roofs indicate upper-middle class.